(untitled) (Al-Aasar, 2025)
This article provides an analytical study of Tawassul, its types, and Shariah evidences. Tawassul is essentially a means of supplicating to Allah Almighty and does not imply attributing independent effectiveness to anyone else. Tawassul is commonly divided into two types: Through righteous deeds (Tawassul bil-A‘maal al-Salihah), and Through virtuous personalities (Tawassul bil-Dhawaat al-Fadhilah). The first type is strongly supported by Qur’an, Hadith, and scholarly consensus. The second type is evidenced through the Prophets, Companions, and pious individuals. Tawassul through the Prophet ﷺ is valid both during his life and, according to most scholars, after his passing. Some critics cite Hazrat Umar’s رضي الله عنه Istisqa’ incident to object to intercession through the deceased, but this does not prohibit it; it only illustrates permissibility in specific circumstances. The study concludes that Tawassul depends on belief in Tawheed; if Allah alone is the true actor and the intermediary is merely a means, it is permissible. Disagreements relate to interpretation of texts, not the permissibility of Tawassul itself. Moderation, good intentions, and scholarly integrity are essential in addressing this matter.